Microseismicity in the period 02/2020-05/2020 at Condor Seamount, Azores (SEISAN waveform files) - Liu, Yingchen; Mitchell, Neil C; Lange, Dietrich; Grevemeyer, Ingo (PANGAEA, 2025)
From February to May of 2020, a seismic network of ocean-bottom seismometers was deployed around the Condor seamount, Azores. This dataset provides waveform event files of 1931 well-located local earthquakes detected in continuous waveform data, with magnitudes between 1.0 and 3.2. The zip-file includes waveform data and a Nordic file, and a station file with station coordinates in SEISAN format. All data in the zipped file can be processed and used with the SEISAN seismology software.
Keywords: Azores; Microseismicity; submarine volcano